Physical Education for women: a gender approach to the 1930s and 40s - Ana Júlia Pinto Pacheco (Revista da Educação Física)
This paper is a gender approach to physical education for women in the 1930s and 40s in order to verify its agreements and contradictions. Revista de Educação Física, issues 1 to 63 (1932-1949), and Educação Physica, issues 1 to 49 (1932-1945), which deal with physical education and physical activities practised by women, supported this reflection. Summing up, the following must be considered: a) the prevailing discourse claimed as biological those features which are basically social while presuposing a kind of physical education adequated to female nature, characteristically limited and light; b) divergencies with this formal thinking believing that female frailty was a cultural consequence and intending a formal physical education which might offer more comprehensive corporal experiences to women must be stressed.